Genetic predisposition to thyroid dysfunction: a case–control study investigating TSHR gene polymorphism (rs2268458) in Indians - Shama Tyagi; Manpreet kaur; Anita yadav; Ranjan Gupta (Egyptian Journal of Medical Human Genetics)
Abstract Background Variations in the TSHR gene have been implicated in a spectrum of thyroid diseases. Previous studies have implicated variations in the TSHR gene, including SNPs rs179247, rs12101255, and rs2268458, in thyroid diseases, but their association with hypothyroidism and hyperthyroidism in the Indian population has not been investigated. Aim In this study, we aimed to examine the relationship between candidate SNP rs2268458 and susceptibility to hypothyroidism and hyperthyroidism in the Indian population. We carried out a case–control genetic screening of the TSHR gene. Methods We analyzed the variant of the TSHR gene using the PCR–RFLP technique in a total of 318 participants, including 130 controls and 188 individuals with thyroid disorders (124 hypothyroid and 64 hyperthyroid). Demographic information was collected, and biochemical parameters were assessed using enzymatic methods. Statistical analysis was performed using SPSS-23. Results The SNP rs2268458 demonstrated a significant association with hypothyroid and hyperthyroid patients (p-value < 0.05). Using the dominant genetic model, we calculated an odds ratio of 3.52 (confidence interval: 2.09–5.93, p-value: 0.0001) for the risk of hypothyroidism and an odds ratio of 2.34 (confidence interval: 1.26–4.31, p-value: 0.0001) for the risk of hyperthyroidism. Conclusion This pioneering study in the Indian population reveals a significant association between the C allele of TSHR gene SNP rs2268458 and an increased risk of developing both hypothyroidism and hyperthyroidism. Our findings suggest that the C allele may be a common genetic risk factor for thyroid dysfunction in Indians.